Facing postmodernity : contemporary French thought on culture and society - Silverman, Maxim (Routledge social futures series., 1999)
Facing Postmodernity explains French cultural theory by grounding it in the politics of the issues facing France today such as: * the breaking of the city * racism * the crisis of culture * new citizenship. It discusses some of the major responses to postmodernity by contemporary French thinkers, both the very well known -Lyotard, Levinas, Derrida - and those who will be less familiar to a non-French audience. In doing so, it addresses the questions central to the postmodern debate whatever country it takes place in; questions of history, of representation, identity and community.